Alkali Chlorides for the Suppression of the Interfacial Recombination in Inverted Planar Perovskite Solar Cells. Issue 19 (25th March 2019) - Chen, Wei; Zhou, Yecheng; Chen, Guocong; Wu, Yinghui; Tu, Bao; Liu, Fang‐Zhou; Huang, Li; Ng, Alan Man Ching; Djurišić, Aleksandra B.; He, Zhubing
Abstract: In this work, significant suppression of the interfacial recombination by facile alkali chloride interface modification of the NiOx hole transport layer in inverted planar perovskite solar cells is achieved. Experimental and theoretical results reveal that the alkali chloride interface modification results in improved ordering of the perovskite films, which in turn reduces defect/trap density, causing reduced interfacial recombination. This leads to a significant improvement in the open‐circuit voltage from 1.07 eV for pristine NiOx to 1.15 eV for KCl‐treated NiOx, resulting in a power conversion efficiency approaching 21%. Furthermore, the suppression of the ion diffusion in the devices is observed, as evidenced by stable photoluminescence (PL) under illumination and high PL quantum efficiency with alkali chloride treatment, as opposed to the luminescence enhancement and low PL quantum efficiency observed for perovskite on pristine NiOx. The suppressed ion diffusion is also consistent with improved stability of the devices with KCl‐treated NiOx. Thus, it is demonstrated that a simple interfacial modification is an effective method to not only suppress interfacial recombination but also to suppress ion migration in the layers deposited on the modified interface due to improved interface ordering and reduced defect density. Abstract : Suppression of the interfacial recombination are achieved by facile alkali chloride modification of the nickel oxide in inverted perovskite solar cells. It is demonstrated that the interface modification induces the ordering of the perovskite crystal at the interfaces, which in turn reduces defect/trap density, causing reduced interfacial recombination. This results in dramatically improvement of the open circuit voltage and power conversion efficiency.